Promoting interdisciplinary shared mental models. (30th March 2018) - Herrmann, Lisa E; Jarvis, Lenore; Bhansali, Priti; Zaveri, Pavan
Summary: Background: Emergency Medicine (EM) and Hospital Medicine (HM) providers frequently interact when transitioning patients from the emergency department (ED) to the inpatient unit; however, there is infrequent collaboration between these subspecialties, and effective communication in EM–HM provider handover is an area for improvement. Shared mental models can enhance communication and safety. The purpose of this article is to describe the implementation of an interdisciplinary conference to allow providers to create shared mental models, and to assess the impact on attitudes and behaviours towards communication and collaboration outside the competing attentions of patient care environments. Methods: The authors instituted a quarterly interactive case‐based conference at an academic tertiary care children's hospital in which EM and HM subspecialty trainees co‐facilitate evidence‐based interactive presentations of clinical, diagnostic or management dilemmas. The conferences were evaluated via repeated cross‐sectional surveys of EM and HM providers, as well as session evaluations. Surveys included multiple‐choice, Likert‐scale and free‐text responses to assess the degree of interaction and collaboration between the divisions and provider attitudes toward changes in clinical practice. Results: Assessment of the EM–HM collaborative conferences demonstrated trends towards increased interaction between divisions and increased discussion about management decisions among colleagues. Two‐thirds of individuals who attended at least one conference felt that having attended an interdisciplinary conference influenced future management decisions. Effective communication in EM–HM provider handover is an area for improvement Conclusions: Interdisciplinary conferences provide a forum for cross‐specialty communication to discuss management differences in a low‐stress educational environment, and allow providers to develop shared mental models for effective, safe patient care.